GR_GERICHTE ZK2 2014 43 vom 16. Juli 2015 , Abänderung des Besuchsrecht - GR Gerichte (2015)
Forderung (Entscheid betreffend Zuständigkeit) | Berufung OR Auftrag/Gesch\x27führung o. Auftrag/Bürgschaft etc.